Model Journal of Self-Care and Mental Well-Being Intervention Strategies in Coping with Technostress in Employees: A Conceptual Study - Norizan Yusof (International Journal of Counseling and Psychotherapy, 2025)
Background: In the digital era, technostress poses a significant challenge to workers' mental well-being and productivity. It refers to the psychological stress from constant technology use, leading to emotional exhaustion, anxiety, and poor work-life balance. Managing its impact is crucial as technology becomes more integrated into the workplace. Objective: This study aims to explore self-care and mental well-being intervention strategies to mitigate the adverse effects of technostress among employees, proposing a conceptual model to address these challenges. Method: Based on the Job Demands-Resources (JD-R) Model, the conceptual model integrates three key components: (1) technostress dimensions (technoload, techno-invasion, and techno-complexity), (2) self-care interventions (mindfulness, mindfulness training, and digital detox), and (3) mental well-being outcomes (reduced stress, increased endurance, and work-life balance). Result: The study suggests that psychological responsiveness and mind-awareness training are critical protective factors against technostress. These interventions help reduce stress, improve endurance, and promote a better work-life balance. Conclusion: This research highlights the significance of self-care strategies in mitigating technostress and enhancing mental well-being in high-tech work environments. Organizations are encouraged to adopt sustainable digital well-being policies. Contribution: This study offers valuable insights into effective interventions for managing technostress, thereby contributing to the development of digital well-being programs in the workplace.